Regioselective Friedel–Crafts Reaction of Electron‐Rich Benzenoid Arenes and Spiroepoxyoxindole at the Spiro‐Centre: Efficient Synthesis of Benzofuroindolines and 2H‐ Spiro[benzofuran]‐3, 3′‐oxindoles. Issue 14 (13th July 2016) - Hajra, Saumen; Maity, Subrata; Roy, Sayan
Abstract: Metal triflate‐catalysed intermolecular Friedel–Crafts reactions involving electron‐rich benzenoid arenes and spiroepoxyoxindoles at the spiro‐centre have been developed for the exclusive regioselective synthesis of 3‐aryl‐(3‐hydroxymethyl)oxindoles with an all‐carbon quaternary centre. Selective ring opening of spiroepoxyoxindoles with phenols provided a direct access to 3‐(hydroxymethyl)‐3‐(2‐hydroxyaryl)oxindoles. We have utilized this methodology successfully as the key step for the synthesis of benzofuroindolines and 2 H ‐spiro[benzofuran]‐3, 3′‐oxindoles. Abstract :